Aseismic effect and parametric analysis of the safe-belt device for a continuous bridge with equal height piers. (15th November 2019) - Fang, Rong; Zhang, Wenxue; Chen, Ying; Zhang, Le
Highlights: The safe-belt device was first proposed and its constitutive model was developed. A vibration table experiment of a three-span continuous bridge was conducted. The aseismic effect and aseismic mechanism of safe-belt device were studied. The parameters of safe-belt device were optimized. Abstract: In order to utilize the potential aseismic capability of the sliding piers and reduce the seismic responses of the fixed pier, the safe-belt device was put forward, which might allow sliding piers to share the seismic load of the superstructure with the fixed pier. A vibration table experiment and simulation of the finite element model (FEM) of a three-span continuous bridge with equal height piers were conducted. Then, the aseismic effect and aseismic mechanism of safe-belt device were studied by taking a five-span continuous bridge with equal height piers as an example. Finally, parameters of safe-belt device were optimized. The results show that the safe-belt device can effectively reduce the seismic responses of the fixed pier in a continuous bridge with equal height piers, but it can greatly increase the seismic responses of the sliding pier at the same time. The acceleration threshold, the tensile stiffness of the brace and the ultimate tension of the brace had great impacts on the aseismic effect of the safe-belt device, so they should be optimized according to the structural characteristics of the bridge and site conditions to obtain a better aseismic effect. The initial gap and the locking gap had little impacts on the aseismic effect of the safe-belt device.